2022
DOI: 10.1002/cbdv.202200160
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modelling and Atomistic Insights into the Binding Mechanism of MmpL3 Mtb

Abstract: Mycobacterial membrane proteins Large (MmpLs), which belong to the resistance, nodulation, and division (RND) protein superfamily, play critical roles in transporting polymers, lipids, and immunomodulators. MmpLs have become one of the important therapeutic drug targets to emerge in recent times. In this study, two homology modelling techniques, Modeller and SWISS-MODEL, were used in modelling the three-dimensional protein structure of the MmpL3 of Mycobacterium tuberculosis using that of M. smegmatis as templ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Other promising MmpL3 inhibitors include indolocarboxamides and adamantylureas. As part of a drug scaffold repurposing program, the cannabinoid receptor modulator rimonabant (Figure 2B) and its diaryl pyrazole analogs were reported to display potent anti-TB activity [45,46]. Arabinogalactan polysaccharide layer.…”
Section: Cell Wallmentioning
confidence: 99%
“…Other promising MmpL3 inhibitors include indolocarboxamides and adamantylureas. As part of a drug scaffold repurposing program, the cannabinoid receptor modulator rimonabant (Figure 2B) and its diaryl pyrazole analogs were reported to display potent anti-TB activity [45,46]. Arabinogalactan polysaccharide layer.…”
Section: Cell Wallmentioning
confidence: 99%
“…Other promising MmpL3 inhibitors include indolocarboxamides and adamantylureas. As part of a drug scaffold repurposing program, the cannabinoid receptor modulator rimonabant (Figure 2B) and its diaryl pyrazole analogs, was reported to display potent anti-TB activity [45,46]. Arabinogalactan polysaccharide layer.…”
Section: Cell Wallmentioning
confidence: 99%
“…Mycobacteria possess a remarkably complex cell envelope consisting of a cytoplasmic membrane and a cell wall, constituting an efficient permeability barrier, which plays a crucial role in intrinsic drug resistance and survival under harsh conditions [7]. Mycobacterium smegmatis (Ms) MmpL3 mutant strains exhibit alterations in cell wall hydrophobicity and growth defects, resulting in resistance to two anti-tubercular agents, SQ109 and AU1235 [8]. The previous study reported that the Rv2686c-Rv2687c-Rv2688c operon, which encodes an ABC transporter in Mtb, conferred Ms resistance to ciprofloxacin [9].…”
Section: Introductionmentioning
confidence: 99%